Business Risk Management Analysis at Warung Mbah Lanang Banyuwangi Using Descriptive Contextual Approach With ISO 31000 Method - Muhammad Rivaldy Hisham; Wisnu Yuwono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Warung Mbah Lanang Banyuwangi is a small and medium business engaged in the food and beverage sector which also implements a Point Of Sales system in its sales activities. However, in implementing the POS system, WMLB must also consider potential risks such as errors in data input, data breaches and theft of POS equipment. Therefore, these risks must be managed properly to reduce the negative impact. In this study, risk analysis was carried out using the ISO 31000 method which includes four stages in the form of identification, analysis, evaluation and treatment of identified risks. The results of the analysis show that the biggest risk is data input errors which result in inaccuracies in transaction data which are the result of a lack of understanding of employees in using the POS system, while the smallest risk is disruption to the system caused by security in the system that has been exploited due to unauthorized access to data and information. Recommendations that can be given to WMLB are to provide intensive training to employees regarding the use of the POS system and practice intensely in using the POS system, as well as routinely backing up data and monitoring inventory properly to avoid delays in sending raw material stocks. while the smallest risk is disruption to the system caused by security on the system that has been exploited due to unauthorized access to data and information. Recommendations that can be given to WMLB are to provide intensive training to employees regarding the use of the POS system and practice intensely in using the POS system, as well as routinely backing up data and monitoring inventory properly to avoid delays in sending raw material stocks, of the smallest risk is disruption to the system caused by security on the system that has been exploited due to unauthorized access to data and information. Recommendations that can be given to WMLB are to provide intensive training to employees regarding the use of the POS system and practice intensely in using the POS system, as well as routinely backing up data and monitoring inventory properly to avoid delays in sending raw material stocks.